Primary School Students’ Analogical Reasoning in Solving Open-ended Word Problems - Egitayanti Aulia Rochman; Mohammad Faizal Amir (Al Ibtida: Jurnal Pendidikan Guru MI)
This study aims to identify primary school students' analogical reasoning in solving open-ended word problems. This is qualitative research with a case study approach. The participants in this study were 25 fifth-grade primary school students selected using the purposive sampling technique to represent each category of analogical reasoning based on analogical reasoning tasks. Research instruments comprised of tests in analogical reasoning tasks and interview guidelines. Data analysis techniques included data reduction, presentation, and verification. Research results showed that there were three categories of students' analogical reasoning in solving word problems with close-ended source problems and open-ended target problems: (1) open comprehensive analogy, where students successfully solved the close-ended source problem and the open-ended target problem; (2) semi-open comprehensive analogy, where students successfully solved the close-ended source problem but did not successfully solve the open-ended target problem; and (3) failure in close-open analogy, where students did not successfully solve the close-ended source problem and the open-ended target problem. The results of this study suggest that educators, especially at the primary level, deepen students' ability to solve close-ended problems first so that students can solve open-ended problems with analogical reasoning.